In-feed supplementation of clinoptilolite favourably modulates intestinal and systemic immunity and some production parameters in weaned pigs - H. Valpotic; S. Terzic; S. Vince; M. Samardzija; R. Turk; G. Lackovic; B. Habrun; D. Djuricic; M. Sadikovic; I. Valpotic (Veterinární Medicína, 2016)
The ban on dietary antibiotic growth promoters (AGP) in swine production has focused increasing research efforts on the development of alternative feed supplements. One such alternative to AGP is the dietary zeolite clinoptilolite (CPL). The aims of this study were to evaluate, in weaned pigs, the effects of CPL on: (a) growth performance, (b) gut health (reduction of harmful bacteria and, incidence/severity of diarrhoea) and (c) circulating or ileal mucosal subsets of lymphoid immune cells, over the course of five weeks post weaning. The non-treated pigs received standard Phase 1 diet from Day 0 to 21 and Phase 2 diet from Day 22 to 35, whereas both diets of experimental pigs were supplemented with 0.5% CPL. The pigs receiving diet supplemented with CPL had significantly higher average daily gain at Day 28 but significantly lower daily gain at Day 35 of the experiment (P < 0.05). The CPL group exhibited non-significantly improved feed conversion ratio (1.83 vs. 2.17) for the total duration of the experiment (Day 0 to Day 35). Although shedding of haemolytic/enterotoxigenic E. coli was more frequent in the CPL group, the sum of their diarrhoea severity score was 12.96% lower (47 vs 54) than that of the non-treated controls. The proportions of circulating lymphoid cell subsets tested (CD45+, CD4+, CD21+), were significantly (P < 0.05 to P < 0.01) higher in CPL-treated pigs between Day 21 and Day 35 of the experiment. Immunohistology/morphometry of ileal segments revealed an increased recruitment of CD45RA+ cells in interfollicular (P < 0.05), but not in follicular areas of ileal PP of CPL-treated pigs at Day 35. In conclusion, CPL did not improve growth in weaned pigs, and generally it failed to improve their feed conversion efficiency. Further, it did not suppress faecal shedding of enterotoxigenic E. coli; however, it was shown to be effective as an immunomodulatory agent by promoting the recruitment of circulating and intestinal immune cell subsets.